2020
DOI: 10.17645/si.v8i2.2810
|View full text |Cite
|
Sign up to set email alerts
|

Falling behind the Rest? China and the Gender Gap Index

Abstract: China’s rank falling in the Global Gender Gap Index of the World Economic Forum has aroused the domestic scholar’s controversy. Based on the data provided by the Global Gender Gap Report, this article will describe the gender inequality in China by comparing its overall index scores and scores in the fields of economic participation and opportunity, education attainment, health and survival, and political empowerment with other countries, and then examining the reasons for China’s falling in rank through the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…The higher the life expectancy indicates, the higher the chances of survival. High health status can affect development [5].This finding is supported by Chen research [10] , which states that increasing women's life expectancy has an impact on gender empowerment, also finds that women's life expectancy, the trend of increasing life expectancy, is generally influenced by the increasing level of health, namely easier access to health facilities. Increasing life expectancy illustrates reduced health inequalities, this reduction in inequality reflects the government's success in efforts to achieve gender equality in the health sector.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…The higher the life expectancy indicates, the higher the chances of survival. High health status can affect development [5].This finding is supported by Chen research [10] , which states that increasing women's life expectancy has an impact on gender empowerment, also finds that women's life expectancy, the trend of increasing life expectancy, is generally influenced by the increasing level of health, namely easier access to health facilities. Increasing life expectancy illustrates reduced health inequalities, this reduction in inequality reflects the government's success in efforts to achieve gender equality in the health sector.…”
Section: Discussionmentioning
confidence: 80%
“…Education will give women better career opportunities and will be able to enhance women's self-confidence to stimulate women's self-determination. Another supporting study by Charmes [4] and Chen [10] found that the…”
Section: Estimate Before Robustmentioning
confidence: 81%
See 1 more Smart Citation
“…The Internet can help build social capital through increasing social interaction with one’s personal social circle irrespective of geographical boundaries (Haythornthwaite, 2005; Wellman et al, 2006). The Internet is frequently used by people for social networking, amusement, knowledge and online transactions due to advancements in affordable mobile devices that allow easy access to the Internet (Cheng et al, 2020). Considered to be among the Internet’s most widespread applications are social networking sites (Statista, 2022c).…”
Section: Background Discussion and Hypotheses Developmentmentioning
confidence: 99%
“…The highest possible score is 1 or 100%, denoting full equality for women, and the minimum score is 0, denoting inequality. Many past studies have also used this index to measure gender equality (Barns & Preston, 2010; Chen & He, 2020; Šestić et al, 2020).…”
Section: Methodsmentioning
confidence: 99%